Exercise restores muscle stem cell mobilization, regenerative capacity and muscle metabolic alterations via adiponectin/AdipoR1 activation in SAMP10 mice. Issue 3 (29th November 2016) - Inoue, Aiko; Cheng, Xian Wu; Huang, Zhe; Hu, Lina; Kikuchi, Ryosuke; Jiang, Haiying; Piao, Limei; Sasaki, Takeshi; Itakura, Kohji; Wu, Hongxian; Zhao, Guangxian; Lei, Yanna; et al.
Abstract: Background: Exercise train (ET) stimulates muscle response in pathological conditions, including aging. The molecular mechanisms by which exercise improves impaired adiponectin/adiponectin receptor 1 (AdipoR1)‐related muscle actions associated with aging are poorly understood. Here we observed that in a senescence‐accelerated mouse prone 10 (SAMP10) model, long‐term ET modulated muscle‐regenerative actions. Methods: 25‐week‐old male SAMP10 mice were randomly assigned to the control and the ET (45 min/time, 3/week) groups for 4 months. Mice that were maintained in a sedentary condition served controls. Results: ET ameliorated aging‐related muscle changes in microstructure, mitochondria, and performance. The amounts of proteins or mRNAs for p‐AMPKα, p‐Akt, p‐ERK1/2, p‐mTOR, Bcl‐XL, p‐FoxO3, peroxisome proliferators‐activated receptor‐γ coactivator, adiponectin receptor1 (adpoR1), and cytochrome c oxidase‐IV, and the numbers of CD34 + /integrin‐α7 + muscle stem cells (MuSCs) and proliferating cells in the muscles and bone‐marrow were enhanced by ET, whereas the levels of p‐GSK‐3α and gp91phox proteins and apoptotic cells were reduced by ET. The ET also resulted in increased levels of plasma adiponectin and the numbers of bone‐marrow (BM)‐derived circulating CD34 + /integrin‐α7 + MuSCs and their functions. Integrin‐α7 + MuSCs of exercised mice had improved changes of those beneficial molecules. These ET‐mediated aged muscle benefits were diminished by adiponectin and AdipoR1 blocking as well as AMPK inhibition. Finally, recombinant mouse adiponectin enhanced AMPK and mTOR phosphorylations in BM‐derived integrin‐α7 + cells. Conclusions: These findings suggest that ET can improve aging‐related impairments of BM‐derived MuSC regenerative capacity and muscle metabolic alterations via an AMPK‐dependent mechanism that is mediated by an adiponectin/AdipoR1 axis in SAMP10 mice.